Corporate governance and its impact on the value-relevance of stock option expense. - Kong, Shujing. (2008)
Employee stock options are commonly used by companies to attract and motivate employees, in the hope of aligning employees’ interests with the shareholders. However, past researches have found mixed reactions from investors with regards to the disclosed stock option expense under SFAS No. 123. This paper seeks to address the value relevance of stock option expense and how it may be affected by corporate governance.